Report of ischemic stroke mimicking isolated ulnar nerve paralysis - Akpinar, Çetin Kürsad; Yilmaz, Ahmet; Dogru, Hakan; Aytaç, Emrah (Turkish Society of Cerebrovascular Diseases, 2016)
The cortical motor hand area is the precentral gyrus. Small cortical infarcts of this area can caused isolated hand weakness. Weakness can consist of either all fingers or ulnar-sided fingers. A 71-year-old man admitted to the emergency department with sudden weakness of the right fourth and fifth fingers Diffusion-weighted brain imaging of a magnetic resonance imaging scan revealed acute infarction of right precentral gyrus. Cardioembolus is the determined ischemic stroke subtype. This report presented a case of ischemic stroke mimicking isolated ulnar nerve paralysis.
Izole ulnar sinir paralizisini taklit eden iskemik inme olgusu
Keywords: Embolism; Precentral grus; Small cortical infarct; Ulnar side